Perancangan Visual Kartu Tarot Untuk Pengenalan Cerita Rakyat Batu Menangis - Limas, Margaretha Angelica; Valentina, Anny (Institut Bisnis dan Teknologi Indonesia, 2024)
Tarot cards are often considered a medium for fortune telling, but in several other countries tarot cards have been socialized with various versions of fairy tales or historical stories of their own countries. Indonesia also has its own tarot cards, namely the Wayang Tarot cards and Nusantara Tarot cards, and has its own community. Tarot cards are widely considered to be a card game for fortune-telling and are synonymous with the word 'mystical', so many people immediately think negatively about tarot cards, even though these cards were originally a game that can now be used as a medium for education through counseling. This design aims to create visual recommendations for tarot cards with illustrations in the form of folklore so that it can reintroduce almost forgotten folklore. The design method used is Robin Landa's method, namely orientation, analysis, design concept, design development, and implementation. The design of this tarot card visual recommendation uses a decorative illustration style emphasizing the use of outlines. The illustrations displayed depict events in the Batu Menangis folklore. This design requires further trials to validate its effectiveness in order to ensure that the tarot cards designed can be a visual recommendation that can reintroduce folklore so that it is not forgotten.